Assessing the Ligand Properties of NHC‐Stabilised Phosphorus(I) Cations. Issue 14 (8th February 2018) - Binder, Justin F.; Kosnik, Stephanie C.; Macdonald, Charles L. B.
Abstract: The isolation and full characterisation of a series of cationic metal–carbonyl complexes bearing an N‐heterocyclic carbene stabilised phosphorus(I) ligand are reported. Specifically, the mononuclear coordination complexes [LM(CO)5 ][BPh4 ] (M=Cr, Mo, W), [LFe(CO)4 ][BPh4 ] and the dinuclear complexes [LMn2 (CO)8 ][BPh4 ] and [LCo2 (CO)6 ][BPh4 ], in which L=[bis(1, 3, 4, 5‐tetramethylimidazol‐2‐ylidene)phosphanide] +, have all been isolated in the solid state and structurally confirmed by single‐crystal X‐ray diffraction. The dicationic platinum complex trans ‐[L2 PtCl2 ][BPh4 ]2 is also reported and fully characterised. The donor ability of [L] + has been assessed by IR spectroscopy of its metal–carbonyl complexes and by using DFT calculations. The results suggest that [L] + is a weak π‐acceptor with moderate donor strength and thus it bridges the gap that exists between phosphines and amines in terms of ligand properties. Collectively, these molecules represent the first crystallographically characterised cationic metal–carbonyl derivatives of a P I ‐centred ligand and are a rare collection of cationic metal–carbonyl complexes. Abstract : Putting phosphorus(I) in a harness ! A series of Group 6 to 9 metal carbonyl complexes of NHC‐stabilised phosphorus(I) cations has been isolated. Assessment of the donor properties of the cationic P I ‐centred ligand by spectroscopic, crystallographic and computational methods places them between those of neutral phosphines and amines.